2008
DOI: 10.4049/jimmunol.180.8.5177
|View full text |Cite
|
Sign up to set email alerts
|

Development of Either Split Tolerance or Robust Tolerance along with Humoral Tolerance to Donor and Third-Party Alloantigens in Nonmyeloablative Mixed Chimeras

Abstract: Hematopoietic chimerism is considered to generate robust allogeneic tolerance; however, tissue rejection by chimeras can occur. This “split tolerance” can result from immunity toward tissue-specific Ags not expressed by hematopoietic cells. Known to occur in chimeric recipients of skin grafts, it has not often been reported for other donor tissues. Because chimerism is viewed as a potential approach to induce islet transplantation tolerance, we generated mixed bone marrow chimerism in the tolerance-resistant N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 60 publications
(74 reference statements)
3
28
0
Order By: Relevance
“…However, because we studied immunity toward the well-defined male Ag that is not tissue-specific, our data would suggest that a form of split tolerance that occurs independently of tissue-specific Ags may be possible and mediated through the variable effectiveness of the indirect CD4 response in eliminating different types of allogeneic grafts. In this regard, diabetes-prone NOD mice demonstrate potent indirect CD4 responses (6,20), and we have recently found that generation of mixed chimerism in NOD recipients can result in a split tolerance characterized by rejection of donor B cells, skin, and islets and survival of donor T cells (66), paralleling the split tolerance data shown here in a TCR transgenic model. Secondly, the susceptibility of B cells to indirect rejection that we have shown here has implications for understanding B cell deletion induced by T cell killing of B cells (67,68).…”
Section: Discussionsupporting
confidence: 76%
“…However, because we studied immunity toward the well-defined male Ag that is not tissue-specific, our data would suggest that a form of split tolerance that occurs independently of tissue-specific Ags may be possible and mediated through the variable effectiveness of the indirect CD4 response in eliminating different types of allogeneic grafts. In this regard, diabetes-prone NOD mice demonstrate potent indirect CD4 responses (6,20), and we have recently found that generation of mixed chimerism in NOD recipients can result in a split tolerance characterized by rejection of donor B cells, skin, and islets and survival of donor T cells (66), paralleling the split tolerance data shown here in a TCR transgenic model. Secondly, the susceptibility of B cells to indirect rejection that we have shown here has implications for understanding B cell deletion induced by T cell killing of B cells (67,68).…”
Section: Discussionsupporting
confidence: 76%
“…For example, isolated Mc in the heart, observed in some NIPA controls ( Figure 1) and in 1 foster-nursed (by B6) NIMA d -exposed offspring (data not shown), may be instead a sign of split tolerance resulting from elimination of professional class II ϩ APCs. 22,23 The immediate postnatal period appears to be critical for establishing a favorable T R Ͼ T E cell balance. When NIMA dexposed mice were foster-nursed by B6 mothers, they lost not only their tolerance to a NIMA-expressing heart allograft, 26 but also MMc (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…21 However, recent experiments have shown that not only the quantity, but also the quality (multilineage vs unilineage) of chimerism is important determining full versus "split" tolerance. 22,23 In addition, the discovery of the "semi-direct" pathway of alloantigen recognition, alloantigen acquisition by host dendritic cells, has provided an amplification mechanism whereby allogeneic cells sequestered in tissues may exert a strong antigenic impact on the host. 24 Yet, if rare maternal cells and antigens are present in professional antigen-presenting cells (APCs), sensitization to NIMA and elimination of maternal cells might be expected to occur in all immunocompetent offspring.…”
Section: Introductionmentioning
confidence: 99%
“…11 Microchimerism itself can be either broadly distributed or narrowly restricted to certain cell lineages. Recently, studies by Chan et al 23,24 suggest that while "full" allograft tolerance is associated with multi-lineage chimerism, a "split tolerance" may result when certain lineages such as T cells are accepted, while B cells and APC are eliminated by the host, resulting in rejection of subsequent skin and islet allografts. The finding that MMc is present in different organs and cell lineages in the NIMA-exposed tolerant offspring in current study suggests that in this breeding model a portion of the offspring have developed a fully tolerant state toward the BDF 1 mother that is maintained during acceptance of a DBA/2 heart allograft.…”
Section: Introductionmentioning
confidence: 99%